Analysis Problem Community Empowerment in Community Awareness Tourism (TASMASDARWIS) Siguntur Old Regency South Coast - Ismaniar, Ismaniar; Aini, Wirdatul; Setiawati, Setiawati; Nora, Desri; Arin, Fitri Dwi; Rozi, Muhammad Fahrur; Landa, Klara Septia (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Activity tourist based potency natural is one of the flagship programs currently encouraged in various area . Because, activities tourist have potency great economy and can influence developments in various sector life society. Existence awareness tourism is needed for support development program success tourist based nature. Because, knowledge, attitude and skills society in general still not yet adequate in Thing the benefits that can be obtained if there is destination tour based nature in the environment. Study this aim for uncover Constraints experienced by the Awareness Society Tour in activity empowerment Public based tour nature in Nagari Siguntur Old, District South Coast. Type study this is study approach case. Data collection techniques combine instruments, interviews and observations as well as analysis document which is various factor or phenomenon connection social in situation certain , describe its uniqueness, and try offer understanding deep that has relevance more wide. Research results show that there are 4 factors the main obstacle activity empowerment community carried out by the community; 1.Mostly TASMASDARWIS management does n't understand each other's TASK, 2. The management of TASMASDARWIS does not alone, 3. Knowledge and skills management still limited in promote location travel,4. Still lacking Support from Public local